Standardless quantification methods in electron probe microanalysis - Trincavelli, Jorge Carlos (2014)
The elemental composition of a solid sample can be determined by electron probe microanalysis with or without the use of standards. The standardless algorithms are quite faster than the methods that require standards; they are useful when a suitable set of standards is not available or for rough samples, and also they help to solve the problem of current variation, for example, in equipments with cold field emission gun. Due to significant advances in the accuracy achieved during the last years, product of the successive efforts made to improve the description of generation, absorption and detection of X-rays, the standardless methods have increasingly become an interesting option for the user. Nevertheless, up to now, algorithms that use standards are still more precise than standardless methods. It is important to remark, that care must be taken with results provided by standardless methods that normalize the calculated concentration values to 100%, unless an estimate of the errors is reported. In this work, a comprehensive discussion of the key features of the main standardless quantification methods, as well as the level of accuracy achieved by them is presented.